Kampus Merdeka: Antara Polemik dan Benefit - Imun, Margareta; Asbari, Masduki; Almuffi, Hafiz; Jebaru, Petrus; Wea, Yanuarius; Sede, Gratiana Rendhebara (AGUSPATI RESEARCH INSTITUTA, 2024)
Kampus Merdeka, an initiative in Indonesian higher education, has sparked intense debate. This article explores the polemics surrounding Kampus Merdeka, including campus autonomy, freedom to choose courses, and education financing, as well as the potential benefits of this initiative. We examine the perspectives of Professor Nizam, the Director-General of Higher Education, who supports the initiative, and Ilham Habibie, the founder of Orbit Future Academy, who sees it as an opportunity to enhance creativity and innovation among students. With careful oversight, Kampus Merdeka has the potential to bring positive changes to Indonesia's higher education landscape.